Cardiopulmonary exercise testing: utility in research and patient care - Raja Ahmad, Raja Elina Afzan; Husain, R.; Lang, C.C. (Faculty of Medicine, University of Malaya, 2005)
Cardiopulmonary exercise testing is a anon-invasive physiological test which incorporates the conventional method of exercise tress test with a more advanced breath-to-breath ventilatory analysis. The physiological parameters obtained from the test help to illustrate the cardiovascular, respiratory and metabolic responses to physical exertion. Individual's functional capacity a nd aerobic fitness is reflected by the value of maximal oxygen consumption (VO2 max) obtained from the cardiopulmonary exercise test. This non-invasive and sophisticated test is regarded as a valuable assessment tool in research and clinical practice. Cardiopulmonary exercise test has been extensively utilized to define the mechanisms of exercise intolerance in various clinical disorders, to evaluate responses to therapy and indicate disease prognosis. Emerging data obtained from the use of the cardiopulmonary exercise testing in the research field, ha led to its extensive clinical usage. It is now utilized as an integral part of the patients' clinical evaluation in the field of respiratory and cardiovascular medicine, sports medicine, surgery as well as occupational and rehabilitative medicine. It has a clinical role in assessing patient's functional capacity, monitoring disease progression and response to the therapy, predicting prognosis, and perioperative morbidity and mortality, as well as constructing and monitoring training and rehabilitative programs. This article aims to give an overview of the physiological profiles obtained from cardiopulmonary exercise testing its methodological aspects, as well as its utility in research and clinical practice.